Candiduria Among Nigerian Women: : A Systematic Review - Korie, M. C.; Echeta, M. O.; Igiri, V. C.; Oyem, I. F.; Unegbu, V. C.; Iheanacho, G. C.; Mbanu, G. E.; Nzeagwu, M. O.; Tony-Nze, C. P.; Itobuchi, C.O. (Journal of Science, Technology and Innovation Research, 2026)
Candiduria is the presence of Candida species in urine samples of patients. It is a public health problem. Therefore the present review was to enrich the data bank of information on candiduria among Nigerian women. Data relating to candiduria and related works were gathered from different search engines including Google scholar, PubMed., Researchgate, African journals online, and Scopus. Other information regarding the prevalence, mode of transmission, pathogenesis, risk factors, signs and symptoms, prevention and control as well as treatments of candiduria were also obtained. Fourteen pooled data studies were extracted using the developed systematic review method which was utilized to analyze the extent of research on canduduria done in Nigeria with regards to the women. Findings by some authors revealed that Candida albican was the most prevalent species found in the urine of most patients. Some Non-albican Candida species were also found in candiduria in some patients. The study also uncovered some risk factors that predisposed the women to candiduria. The study recommends more research on Candiduria in all the geopolitical zones of the country to suggest likely preventive approaches to reduce the rate of infection among women. Keywords: Candiduria, Candida, Women, Nigeria.